Feasibility of using a photoelectric sensor combined with density measurements for nondestructive assessment of the freshness of Hen's eggs - Teerachaichayut, S.; Pansiri, J.; Nguanprasert, P.; Thepwapee, W. (My University, 2018)
Quality of hen's eggs relates to their storage time. Freshness of hen's eggs is an important quality but it cannot be determined by a visual inspection, the only way is to take a sample from a batch of eggs and test the sample destructively by the internationally accepted Haugh method. This study used a photoelectric sensor in order to test whether it could be used as a nondestructive test to detect the freshness of hen's eggs when combined with measurement of their density by displacement in water. Eggs were stored at 25°C for up to 20 days and each egg was tested at intervals first with the photoelectric sensor, then their density was measured and finally each egg was broken and subject to the Haugh test. A training set (N=64) was used to establish a model for predicting the freshness of the eggs based on storage time using multiple linear regression. A test set (N=32) was used to test the model. The model had a coefficient of determination (R2) of 0.881 and the root mean square error of prediction (RMSEP) of 2.36 days. This showed that the photoelectric sensor combined with density measurements could be used to develop a model that gave reliable results for nondestructive prediction of the freshness of hen's eggs and how this changed during storage.
Keywords: density; Haugh unit; light and signal; model